Underlying Structure of Ruminative Thinking: Factor Analysis of the Ruminative Thought Style Questionnaire - Tanner, Alicia; Voon, David; Hasking, Penelope; Martin, Graham (Springer New York, 2013)
The Ruminative Thought Style Questionnaire (RTSQ) is a 20-item measure assessing a single dimension of rumination over and above valence, temporal orientation of thought content, and the cognitive-affective context in which it occurs. The current study examined the factor structure of rumination as measured by the RTSQ, and whether findings of its initial validation study could be replicated within an adolescent sample (N = 2,362). An exploratory factor analysis and a subsequent confirmatory factor analysis were undertaken on two subsamples (n = 1,181) which did not significantly differ in gender and age. Five items with factor loadings of <.50 or cross loadings of >.30 on a second factor were removed. As hypothesised, an exploratory factor analysis on the final 15items demonstrated the RTSQ was comprised of four rumination subcomponents, labelled ‘‘Problem-Focused Thoughts’’, ‘‘Counterfactual Thinking’’, ‘‘Repetitive Thoughts’’, and ‘‘Anticipatory Thoughts’’. A confirmatory factor analysis supported this, contrary to the initial validation study. Each of these subscales had differential contributions to psychological distress and coping styles in separate multiple regressions. Our findings support the increasing body of evidence suggesting a multidimensional structure for rumination, and clinical implications are noted.